Drug resistance in Candida albicans isolates and related changes in the structural domain of Mdr1 protein - P. Dhasarathan; Mohamad S. AlSalhi; Sandhanasamy Devanesan; Jeeva Subbiah; A.J.A. Ranjitsingh; Mohammed Binsalah; Akram A. Alfuraydi (Elsevier, 2021)
Background: The increasing azole drug resistance in fungal pathogens poses a pressing threat to global health care. The coexistence of drug-resistant Candida albicans with tuberculosis patients and the failure of several drugs to treat C. albicans infection extend hospital stay, economic burden, and death. The misuse or abuse of azole-derived antifungals, chronic use of TB drugs, different immune-suppressive drugs, and diseases like HIV, COVID-19, etc., have aggravated the situation. So it is vital to understand the molecular changes in drug-resistant genes to modify the treatment to design an alternative mechanism. Method: C. albicans isolated from chronic tuberculosis patients were screened for antifungal sensitivity studies using disk diffusion assay. The multidrug-resistant C. albicans were further screened for molecular-level changes in drug resistance using MDR1 gene sequencing and compared with Gen bank data of similar species using the BLAST tool. Results: The investigation proved that the isolated C. albicans from TB patients are significantly resistant to the action of six drugs. The molecular changes in MDR1 genes showed differences in seven nucleotide base pairs that interfered with the efflux pump.